Differences in tensile adhesion strength between HEMA and nonHEMA-based dentin bonding applied on superficial and deep dentin surfaces - Eresha Melati Kusuma Wurdani; Adioro Soetojo; Devi Eka Juniarti (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: Improvement in dentistry shows some progresses, due to patients awareness on the importance of dental care. Cervical lesion is the most common phenomenon which oftenly found 46.36% in man and 38.13% in woman. Cervical lesions need composite restoration for treatment to stop the process of tissue damage. The process of adhesion of composite restoration material to the structure of the tooth is not easily separated and it needs optimal function in the oral cavity. Application of dentin bonding agents to attach the composite is needed. Selection of HEMA-based bonding material and Hema free-based bonding material which have a different solvent in their composition, as applied to the dentin superficial and deep dentin, affect the results of debonding test. Debonding test is done to measure the adhesion strength of a bonding material. Purpose: The purpose of this study was to analyze differences in tensile bond strength of dentine bonding HEMA-based and HEMA-free based after application in superficial and deep dentine surfaces. Method: The tooth of the bovine was as samples. A superficial dentine sample was taken from 0.5-1 mm of dentino enamel junction and a deep dentine sample was taken from 0.5 mm culmination of pulp horn. Dentine surface area was equal to p x r2 = (3.14 x 22) = 12.56 mm2. Six samples of HEMA-based bonding was applied to the dentine superficial. Six samples of HEMAfree based bonding was applied to the superficial dentine. Six samples of HEMA-based bonding was applied to the deep dentine. Six samples of HEMA-free based bonding was applied to the deep dentine. Tensile strength was measured using an Autograph AG-10TE. Result: There were differences tensile bond strength of dentine bonding HEMA-based and HEMA-free based after the application on superficial (p=0.000) and deep dentine surfaces (p=0.000). Conclusion: There were differences tensile bond strength of dentine bonding HEMA-based and HEMA-free based after the application on superficial and deep dentine surfaces. The use of dentine bonding materials HEMA-free based were better than HEMA-based after application on different dentine depths.